Development of Augmented Learning Media Reality for Students Learning Difficulties in Elementary School - Angreni, Siska; Sari, Rona Taula; Masyitah, Ike (Journal of ICSAR, 2023)
This study aims to produce interactive augmented reality media in science learning for students with special needs that are valid and practical. To achieve the goal, the method used is the research and development method, adopting the ADDIE model, namely 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The instrument used is the validity observation sheet and the practicality observation sheet. Based on data analysis, it was found that the validity of the Augmented Reality-based learning media for fifth grade elementary school students that was developed was declared valid with an average score of 3.32. Therefore, this learning media can be used as a supporting tool in the learning process in class V elementary school. Practicality The learning media based on Augmented Reality for grade V Elementary School students that was developed was stated to be very practical with a percentage of 91.8% consisting of 90.6% of teacher response questionnaires and 93.2% of student response questionnaires, so that augmented reality-based learning media developed belongs to the very practical category, so this media can be used as one of the learning materials, especially in science subjects on the water cycle material for fourth grade elementary school students.